Математичне моделювання та просторовий аналіз процесів емісії парникових газів у промисловому та сільськогосподарському секторах Польщі - Чарковська, Надія Василівна (Національний університет "Львівська політехніка", 2015)
Дисертація присвячена розробленню математичних моделей для здійснення просторового аналізу процесів емісії парникових газів при виробництві промислової продукції та веденні сільського господарства, а також при оперуванні з відходами у Польщі, які дають можливість враховувати особливості кожного джерела емісії та його географічне розміщення. Розроблено математичні моделі процесів емісії парникових газів у промисловому секторі, які базуються на представленні крупних підприємств точковими джерелами, а населених пунктів з великою кількістю дрібних підприємств харчової галузі – площинними джерелами емісії. Розроблено математичні моделі процесів емісії парникових газів у сільськогосподарському секторі, які базуються на представленні поголів’я домашніх сільськогосподарських тварин і сільськогосподарських угідь площинними джерелами емісії. Здійснено просторовий аналіз емісій парникових газів у промисловому та сільськогосподарському секторах Польщі з використанням геоінформаційних технологій, а також аналіз невизначеності результатів просторової інвентаризації парникових газів у цих секторах з врахуванням особливостей кожного джерела емісії. Диссертация посвящена разработке математических моделей для осуществления пространственного анализа процессов эмиссии парниковых газов при производстве промышленной продукции и ведении сельского хозяйства, а также при оперировании с отходами в Польше, которые дают возможность учитывать особенности каждого источника эмиссии и его географическое положение. Разработаны математические модели процессов эмиссии парниковых газов в промышленном секторе, которые базируются на представлении крупных предприятий точечными источниками эмиссии, а населенных пунктов с большим количеством мелких предприятий пищевой отрасли – плоскостными источниками эмиссии. Разработаны математические модели процессов эмиссии парниковых газов в сельскохозяйственном секторе, которые базируются на представлении поголовъя домашних сельскохозяйственных животных и сельскохозяйственных угодий плоскостными источниками эмиссии. Осуществлен пространственный анализ эмиссий парниковых газов в промышленном и сельскохозяйственном секторах Польши с использованием геоинформационных технологий, а также анализ неопределенности результатов пространственной инвентаризации парниковых газов в этих секторах с учетом особенностей каждого источника эмиссии. This thesis addresses the development of mathematical models for spatial analysis of greenhouse gas (GHG) emission processes in the production of industrial goods, the agricultural activity, as well as the waste handling in Poland, which make it possible to take into account the features of each emission source and its geographical location. In the first chapter, known approaches and methods for modeling of greenhouse gas emission processes in Industrial, Agricultural and Waste sectors have been analyzed. The overview of main methodologies of GHG inventory has been done. The expediency of the development of GHG spatially distributed inventory, which gives the possibility to build the spatial emission cadastres and get the new knowledge on real emission structure in studied sectors, has been justify. In the second chapter, the mathematical models of greenhouse gas emission processes in the industrial sector, based on presenting of large industrial enterprises as point-type emission sources, and the settlements with a large number of small enterprises of food industry as area-type emission sources, have been developed. In the third chapter, the mathematical models of the greenhouse gas emission processes in the agricultural sector, based on presenting of domestic livestock and agricultural lands as area-type sources of emissions, have been developed. The fourth chapter deal with modeling of greenhouse gas emission processes in waste handling. The mathematical models for GHG spatial inventory at elementary objects’ level were developed. The algorithms of disaggregation of statistical data have been created. On the base of these algorithms the geospatial database of industrial production plants, agricultural lands, and territories of urban settlements as emission sources has been formed. The numerical experiments on mathematical modeling of GHG emission processes were performed. The spatial analysis of greenhouse gas emissions in the industrial and agricultural sectors, and handling of waste in Poland, using geoinformation technologies, has been implemented. In the fifth chapter, the uncertainty analysis of the inventory results of greenhouse gas emissions in studied sectors, taking into account the characteristics of each emission source, has been carried out. The Monte Carlo approach and 95% confidence intervals were used for uncertainty estimation.
Математическое моделирование и пространственный анализ процессов эмиссии парниковых газов в промышленном и сельскохозяйственном секторах Польши
Mathematical modeling and spatial analysis of greenhouse gas emission processes in the industrial and agricultural sectors of Poland
Keywords: математичне моделювання; процес емісії парникових газів; промисловий сектор; сільськогосподарський сектор; оперування з відходами; невизначеність результатів моделювання; математическое моделирование; процесс эмиссии парниковых газов; промышленный сектор; сельскохозяйственный сектор; оперирования с отходами; неопределенность результатов моделирования; mathematical modeling; process of greenhouse gas emission; Industrial sector; Agricultural sector; Waste sector; uncertainty of modeling results